Potassium-bearing, fluorine-rich tourmaline from metamorphosed fluorite layer in leucocratic orthogneiss at Nedvedice, Svratka Unit, western Moravia - Novak,M.; Selway,J.B.; Houzar,S. (Journal of the Czech Geological Society, 1998)
Three tourmaline parageneses occur in orthogneiss and associated rocks at Nedvedice: i) columns of black tourmaline, locally corroded, show patchy zoning with schorl > schorl cores, and occur in a metamorphosed fluorite layer; ii) black columnar crystals of accessory to subordinate homogeneous schorl from leucratic orthogneiss are locally concentrated in thin bands or in elongated clusters with quartz and muscovite; iii) black columnar tourmaline crystals with schorl > dravite rims and dravite > schorl cores are heterogenous in thin section and BSE images, and occur in muscovite >> biotite schists. Tourmaline from all three parageneses is characterized by high F (up to 0.77 apfu) and K (up to 0.09 apfu) in tourmaline from the metamorphosed fluorite layer. Two dominant substitutions were recognized in tourmaline: 1) Fe Mg substitution in schorl-dravite from mica schists and metamorphosed fluoroite layer; and 2) OH F substitution tyopical for tourmaline from all rock types. Potassium rarely substitutes for Na at the X-site in the tourmaline structure. The chemical compositions suggest that K Na, KFe3+ NaAl and/or NaFe2+OH KFe3+O substitutions may be responsible for K in tourmaline from Nedvedice.
Keywords: tourmaline; electron microprobe; metamorphosed fluorite layer; orthogneiss; mica schist; Nedvedice; Svratka Unit; Czech Republic